China's outward FDI: An industry-level analysis of host country determinants - Alessia Amighini; Roberta Rabellotti; Marco Sanfilippo (Center for Economic Studies and ifo Institute (CESifo), 2011)
We provide an empirical analysis of host country determinants of Chinese outward FDI for the period 2003 to 2008, using data disaggregated by country and industry. We want to assess the relevance of market-seeking, resource-seeking and strategic asset seeking motivations suggested by the theory on FDI determinants. Our results show that only FDI in manufacturing is attracted by market seeking motivations. As expected, resource seeking is an important motivation for Chinese FDI in resource related sectors, which usually refers to countries with political fragile environments. Strategic asset seeking motivations are relevant for both manufacturing and services.
Keywords: F14; F21; 330; China; foreign direct investment; internationalization; trade-FDI nexus; Direktinvestition; Chinesisch; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Branche; Rohstoffressourcen; China; Welt